Pengaruh Kepemimpinan Spiritual Terhadap Perilaku Etis, Kualitas Kehidupan Kerja, Kepuasan Kerja, Komitmen Organisasional dan Kinerja Karyawan [Influence of Spiritual Leadership on Ethical Behavior, Quality of Work Life, Job Satisfaction, Organizational Commitment, and Employee Performance] - Riane Johnly Pio; Umar Nimran; Taher Alhabsji; Djamhur Hamid (Universitas Pelita Harapan, 2015)
This study aims to analyze and explain the influence of spiritual leadership to ethical behavior, quality of work life, job satisfaction, organizational commitment and employee performance. The sample in this study was 160 employees working at the Bank of North Sillawesi. Structural Equation Modeling was used as a tool of analysis in this study. The results showed that spiritual leadership had significant influence directly to ethical behavior, but no significant effect on the quality of work life, job satisfaction, organizational commitment and employee performance. Ethical behavior has a direct significant effect on the quality of working life, job satisfaction, and organizational commitment, and indirectly significant effect on employee performance. Quality of work life has a significant direct effect on job satisfaction, organizational commitment and employee performance. Job satisfaction has a direct significant effect on organizational commitment and indirectly has a significant effect on the perforrnance of employees. Organizational commitment has a direct significant effect on the performance of the employee. The findings in this study are the spiritual leadership affects the quality of work life, job satisfaction and organizational commitment through ethical behavior. Spiritual leadership affects the performance of employees through ethical behavior and organizational commitment. Ethical behavior influences employee performance through organizational commitment, and job satisfaction influence on employee performance through organizational commitment.